Double-Opposing Unilobar Rotation Flaps in the Reconstruction of Moderate-to-Large Defects of the Scalp. Issue 6 (September 2015) - Moulton-Barrett, Rex; Vanderschelden, Benjamin
<x xml:space="preserve">Abstract</x> Abstract Closure of medium-to-large-size defects of the scalp are often associated with unacceptable aesthetic results, wound break down, alopecia, and excessive scarring. The authors present 2 cases of double-opposing unilobar rotation flaps for the reconstruction of large, that is, at least 7 cm diameter, full thickness defects of the scalp. Unlike previously described double flap closures of scalp defects, the double-opposing unilobar rotation flap design are true rotation flaps, which require a Burow triangle excisions and which have a versatility in both width and length of design to accommodate closure of large defects of the scalp. Some of the advantages of this technique are the retention of hair-bearing skin without distortion of the follicle position, an aesthetically pleasing scar, minimal tension at the wound closure site, and the versatility as well as simplicity of the technique.